Composition of the volatiles of locally grown cultivars of Allium cepa L. (Fam. Liliaceae) and their oral hypoglycemic action - Agu, Longinus O. Madojemu 1952-
A yellow oil, slightly tinged with various colors, was obtained from the etheral extract of four varieties of skin-free onion bulb (Allium cepa L. Fam. Liliaceae) at an average yield of 0.073%, 0.043%, 0.041%, and 0.054% on a fresh weight basis for the red, yellow, purple, and white cultivars, respectively. The following physico-chemical properties--refractive index, optical rotation, solubility in different solvents, acid value, saponification value, and ester value--were determined for the oil from the red and yellow cultivars of onion. Gas chromatographic analysis of the headspace gas of the four cultivars showed the presence of methyl sulfide, methyl disulfide propane thiol, and propyl disulfide while in the onion oil, only propyl disulfide was identified. The petroleum ether nonsoluble fractions of red (17.64%) and yellow (22.41%) from onion oil produced significant hypoglycemic effect when administered orally to rabbits. Methyl sulfide does not show any significant hypoglycemic effect.
Available to the general public.
Thesis (Master of Science in Pharmaceutical Chemistry)--University of the Philippines Manila, December 1984.
Keywords: Onions; Essences and essential oils